1991
DOI: 10.1007/bf03008614
|View full text |Cite|
|
Sign up to set email alerts
|

Transcranial doppler sonography: nitrous oxide and cerebral blood flow velocity in children

Abstract: To determine the effect of nitrous oxide (NzO) on cerebral blood flow velocity (CBFV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
(5 reference statements)
3
18
0
Order By: Relevance
“…This is in contrast to the global cerebral vasodilatation produced by CO 2 (46,47). The exact mechanism behind this cerebral vasodilatation is not known, however, mitochondrial activation (46,53,54,58,59), and sympathoadrenal stimulation (60,61) have been suggested. According to the experimental data, N 2 O increases CMRO 2 when given alone (62) or in combination (63-65) with other anesthetic drugs.…”
Section: Pharmacologymentioning
confidence: 95%
See 2 more Smart Citations
“…This is in contrast to the global cerebral vasodilatation produced by CO 2 (46,47). The exact mechanism behind this cerebral vasodilatation is not known, however, mitochondrial activation (46,53,54,58,59), and sympathoadrenal stimulation (60,61) have been suggested. According to the experimental data, N 2 O increases CMRO 2 when given alone (62) or in combination (63-65) with other anesthetic drugs.…”
Section: Pharmacologymentioning
confidence: 95%
“…More specifically, N 2 O increases regional CBF and regional CBV in supratentorial grey matter. This is in contrast to the global cerebral vasodilatation produced by CO 2 (46,47). The exact mechanism behind this cerebral vasodilatation is not known, however, mitochondrial activation (46,53,54,58,59), and sympathoadrenal stimulation (60,61) have been suggested.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…These results correspond well with earlier CBF and cerebral blood flow velocity measurements which showed that equipotent doses of different inhalation anaesthetics, ranging up to 1 MAC in oxygen/air, comparably affect cerebral perfusion. Distinct effects on cerebral perfusion were found when patients received different inhalational anaesthetics in higher doses (> 1 MAC) and especially when nitrous oxide is given simultaneously [23–27]. Thiel et al .…”
Section: Discussionmentioning
confidence: 99%
“…Volatile anaesthetics such as halothane, isoflurane, or even nitrous oxide can also influence cerebrovascular resistance and vascular tone. Comparative studies have shown that these anaesthetics can induce totally different substance‐specific and dose‐dependent changes in cerebral circulation during general anaesthesia [23–28]. Human clinical investigations on the potential interactive effects of theophylline and volatile anaesthetics on cerebral perfusion during general anaesthesia have not yet been published.…”
Section: Introductionmentioning
confidence: 99%